2013
DOI: 10.1002/idj.12004
|View full text |Cite
|
Sign up to set email alerts
|

Trends in endodontic claims in Italy

Abstract: According to the scant data available in the literature, endodontic claims are common among dental professional liability cases and the second most common type of claim. This study aimed to describe the characteristics of endodontic claims in Italy and the most frequently disputed errors, and the discussion below includes consideration of ethical and medico-legal aspects thereof. We retrospectively analysed 120 technical reports written on cases of professional malpractice in endodontics in the last 5 years. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 24 publications
2
22
0
2
Order By: Relevance
“…This case describes the extremely rare event of hemidiaphragm paralysis after surgery on sites distant from there, which has been seldom reported in literature. This article aims at both improving the knowledge of clinicians focusing attention on postsurgical symptoms of these cases and providing useful evidence for preventing unfair, expensive and stressful medico-legal litigation [24,25] .…”
Section: Resultsmentioning
confidence: 99%
“…This case describes the extremely rare event of hemidiaphragm paralysis after surgery on sites distant from there, which has been seldom reported in literature. This article aims at both improving the knowledge of clinicians focusing attention on postsurgical symptoms of these cases and providing useful evidence for preventing unfair, expensive and stressful medico-legal litigation [24,25] .…”
Section: Resultsmentioning
confidence: 99%
“…A "frustrating patient visit" [ 28 ] may develop when a treatment decision regarding the "complaint tooth" has to be carried out, and in case of a crucial relationship deterioration between the practitioner and the patient, irrational treatment solutions, such as to extract the tooth, may be chosen [ 2 ]. For example, it had been reported that almost 50 % of teeth with a short root fi lling, almost 90 % of perforated teeth, and all teeth diagnosed with a separated instrument were extracted [ 4 ]. However, for the vertical root fracture, it may be the opposite way around-the tooth has typically been extracted because it is untreatable and then a medicolegal scenario may arise shortly after.…”
Section: The Fate Of the "Complaint Tooth" In Relation To Vertical Romentioning
confidence: 98%
“…Endodontic treatment-related claims are among the top three frequent reported complaint areas [ 2 ], and among specifi c causes for these complaints, are vertical root fractures [ 4 ].…”
Section: Dental Areas Of Malpractice Claimsmentioning
confidence: 99%
“…Notably, oral surgery seems to be lesser involved within recent years, whereas implant placements are a new growing area of malpractice complaints. The latest report has implant as the number one most frequent claim area [ 9 ].…”
Section: Areas Of Malpractice Claimsmentioning
confidence: 99%